Characteristics and clinical outcome of breast cancer patients with asymptomatic brain metastases - Laakmann, Elena; Witzel, Isabell; Neunhöffer, Tanja; Weide, Rudolf; Schmidt, Marcus; Park-Simon, Tjoung Won; Möbus, Volker; Mundhenke, Christoph; Polasik, Arkadius; Lübbe, Kristina; Hesse, Tobias; Riecke, Kerstin; et al. (Cancers, 2020)
Background: Brain metastases (BM) have become a major challenge in patients with metastatic breast cancer. Methods: The aim of this analysis was to characterize patients with asymptomatic BM (n = 580) in the overall cohort of 2589 patients with BM from our Brain Metastases in Breast Cancer Network Germany (BMBC) registry. Results: Compared to symptomatic patients, asymptomatic patients were slightly younger at diagnosis (median age: 55.5 vs. 57.0 years, p = 0.01), had a better performance status at diagnosis (Karnofsky index 80–100%: 68.4% vs. 57%, p < 0.001), a lower number of BM (>1 BM: 56% vs. 70%, p = 0.027), and a slightly smaller diameter of BM (median: 1.5 vs. 2.2 cm, p < 0.001). Asymptomatic patients were more likely to have extracranial metastases (86.7% vs. 81.5%, p = 0.003) but were less likely to have leptomeningeal metastasis (6.3% vs. 10.9%, p < 0.001). Asymptomatic patients underwent less intensive BM therapy but had a longer median overall survival (statistically significant for a cohort of HER2-positive patients) compared to symptomatic patients (10.4 vs. 6.9 months, p < 0.001). Conclusions: These analyses show a trend that asymptomatic patients have less severe metastatic brain disease and despite less intensive local BM therapy still have a better outcome (statistically significant for a cohort of HER2-positive patients) than patients who present with symptomatic BM, although a lead time bias of the earlier diagnosis cannot be ruled out. Our analysis is of clinical relevance in the context of potential trials examining the benefit of early detection and treatment of BM.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Asymptomatic; Brain metastases; Breast cancer